Acquisition of Numeracy Manipulative Skills for National Development in North-central, Nigeria - Jimoh, Idris Mohammed (International Journal of Evaluation and Research in Education (IJERE), 2022)
Education is an instrument that empowers an individual to become a useful member of the society through the acquisition of basic skills, abilities, attitudes so that they can be self-reliance and self-supportive. The study therefore, examined numeracy manipulative skills for national development among basic students in North-central, Nigeria. This study adopted a descriptive survey research design using Tyler evaluation model of 1949. The population of the study comprised all students of Universal Basic Education schools while the target population consisted of 645,177 upper basic students in North-central, Nigeria. Four purposes, one research question and three hypotheses were raised. Self-developed Numeracy Manipulating Test was used for data collection contained thirty items. Psychometric properties were determined using content validity, obtained 0.88 S-CVI, and split-half reliability estimate using Kuder Richardson KR 20 formula and obtained a 0.81 reliability coefficient. The research question was answered using percentage while hypotheses were tested using an independent t-test at 0.05 level of significance. TheÂ findings revealed that upper basic students in North-central, Nigeria possessed 41.61% numeracy manipulating skills. No significant differences existed between male (47.30%) and female (48.53%); a significant difference existed based on school ownership (public-35.27% and private-49.61%) and location (rural-36.95% and urban-48.72%) at 0.05 level of significance. It was concluded that the performance of students was weak and might inhibit national development. It was recommended that the Nigerian governments at all levels should give more priority to the UBE programme because it is the foundation upon which other levels of education are built.